PERAN KOMUNIKASI PEMBANGUNAN DALAM PEMBERDAYAAN MASYARAKAT TANI DI REMBANG - Priska Nur Safitri (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2019)
This study aims to determine and analyze the role of development communication in the empowerment of peasant communities in Rembang. The focus of this study is on the role of agricultural development communication in the village of Dadap Mulya, Sarang, Rembang. Data collection techniques include documentation, observation, and interviews. This study concludes that communication carried out is still conventional logic so that it requires empowerment with a biotechnology digitization system. Technology with good accessibility will result in the availability of mass production. Based on real conditions, farmers must make better agricultural innovations. Therefore, the researchers offered a VAD Model for empowering peasant communities. VAD is considered suitable when applied to the quality of its human resources. Improving the quality of human resources can be done through socialization, training, teaching, and direct practice. The VAD model is considered suitable because in operation it involves physical to virtual, human to autonomus, and intermediacy to disentermediacy.